Rotating green wall a practical, cost-effective, and user-friendly vertical gardening alternative - Tuazon, Paolo G.; Villa Juan, Jose Dan (Quezon City College of Architecture, University of the Philippines Diliman, 2015)
Access to the upper parts of the present day designs for green walls has always posed a major challenge in maintaining and sustaining vertical gardens which has led to costs in both money and time. This study was conducted to develop an alternative green wall system to improve access using an alternative green wall system that is both cost-effective and user-friendly. The study involved two main phases, namely, research and development of the prototype rotating green wall system and the construction of a more traditional green wall (as control) and data collection at Bay, Laguna and UP Diliman. A total of 55 randomly selected subjects were asked to water plants from the two types of green walls. Variables measured were before and after measurements of pulse and heart rates using a digital blood pressure monitor, perception of ease of use and preferences using Borg RPE Scale and duration for watering both systems. Results of the study showed that the developed rotary system was preferred when compared to the traditional system except that the former was more expensive due to the pulley system installed. However, the rotary system had less damaged plants. Although not measured by the study, it is probable that the health and reduction in risks due to using ladders may outweigh the initial cost of setting up the rotary system. It is recommended that this prototype be scaled up to further explore its effectiveness under conditions simulating higher placements as well as explore alternative materials which can help reduce cost. Other parameters should also be studied like water efficiency of this model in the light of problems of water availability, as well as research in other possible applications such as in residential areas in urban areas like condominiums where space is limited and use of edible plants to help address food security particularly in urban slums.
Includes appendices
Thesis (Master of Tropical Landscape Architecture) -- University of the Philippines Diliman